Mastering your fellowship (Online) - Mergan Naidoo; Langalibalele Honey Mabuza; Andrew Ross; Beverley Schweitzer (South African Family Practice, 2017)
The series, “Mastering your Fellowship”, provides examples of the question format encountered in the written Final Part A of the FCFP (SA) examination. The series is aimed at helping family medicine registrars prepare for this examination. Model answers are available online.